Issues of Speech Culture in Navoi's Work - Dildora Azodovna Bakhadirova (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In this article, Navai realized that language is a growing and developing necessity that meets the needs of the society. In the work